Streptokinase Treatment Reverses Biofilm-Associated Antibiotic Resistance in Staphylococcus aureus - Jørgensen, Nis Pedersen (Microorganisms, 2016)
Biofilms formed by Staphylococcus aureus is a serious complication to the use of medical implants. A central part of the pathogenesis relies on S. aureus’ ability to adhere to host extracellular matrix proteins, which adsorb to medical implants and stimulate biofilm formation. Being coagulase positive, S. aureus furthermore induces formation of fibrin fibers from fibrinogen in the blood. Consequently, we hypothesized that fibrin is a key component of the extracellular matrix of S. aureus biofilms under in vivo conditions, and that the recalcitrance of biofilm infections can be overcome by combining antibiotic treatment with a fibrinolytic drug. We quantified S. aureus USA300 biofilms grown on peg-lids in brain heart infusion (BHI) broth with 0%–50% human plasma. Young (2 h) and mature (24 h) biofilms were then treated with streptokinase to determine if this lead to dispersal. Then, the minimal biofilm eradication concentration (MBEC) of 24 h old biofilms was measured for vancomycin and daptomycin alone or in combination with 10 µg/mL rifampicin in the presence or absence of streptokinase in the antibiotic treatment step. Finally, biofilms were visualized by confocal laser scanning microscopy. Addition of human plasma stimulated biofilm formation in BHI in a dose-dependent manner, and biofilms could be partially dispersed by streptokinase. The biofilms could be eradicated with physiologically relevant concentrations of streptokinase in combination with rifampicin and vancomycin or daptomycin, which are commonly used antibiotics for treatment of S. aureus infections. Fibronolytic drugs have been used to treat thromboembolic events for decades, and our findings suggest that their use against biofilm infections has the potential to improve the efficacy of antibiotics in treatment of S. aureus biofilm infections.